Using 'Paddy Field' Graphic Organiser to Enhance Students' Ability in Expanding and Simplifying Algebraic Expressions - Lim Yi Wei (Southeast Asian Mathematics Education Journal, 2020)
The purpose of this action research was to enhance students' abilities in expanding and simplifying algebraic expressions. A total of 26 students from 3 Anggerik (9th Grade) SMK SANZAC, Malaysia, were involved in this action research. Based on the analysis of their marks from the previous test and mid-year examination, they were unable to solve algebraic expressions, even though they had learnt them since Form 1(7th Grade). However, expanding and simplifying algebraic expressions are fundamental to solving mathematics problems, with approximately 46% of lower form mathematic topics requiring these skills. Hence, the "Paddy Field" method was introduced to help students expand and simplify algebraic expressions. Post-test results showed a significant improvement in students' abilities to expand and simplify algebraic expressions.